Saffron induces Apoptosis in Ovarian Cancer cell via MAPK and AKT/mTOR Pathways: Saffron for ovarian cancer - Guler Okyay, Ayse; Kaplan, Halil Mahir; Asil, Hasan; Singirik, Ergin (Progress in Nutrition, 2020)
Study Objectives: Saffron and its main components have been shown to have anti-tumor and anticancer effects in animal studies and human cancer cell cultures. This study aimed to investigate the anti-cancer effects of saffron on human ovarian cancer cells. Methods: Powder of saffron was applied to the HO–8910 cell lines. Cell viability was determined. ELISA test is used to examine the activity of caspase-3 and expression of AIF, gadd153, grp78, caspase 3, bax, bcl-2, wee 1, which are apoptotic pathway’s mediators. Active ERK (p-ERK), active JNK (p-JNK) active AKT (p-AKT), and active mTOR (p-mTOR) were also analyzed by ELISA. Results: Saffron treatment reduced the viability of ovarian cancer cells. Saffron treatment increased activity of caspase 3 and expression of bax, wee 1, gadd153, grp78, and AIF and decreased bcl-2 which is anti-apoptotic protein. Saffron also decreased the activity of p-ERK, p-JNK, p-AKT, and p-mTOR in ovarian cancer cells. Conclusion: This study revealed that saffron has a beneficial effect on cancer treatment. Saffron may show a synergistic effect with various chemotherapeutics while directing the cancer cell to death. Crocetin, one of its active components, has shown a synergistic anti-cancer effect combined with cisplatin. Saffron induced apoptosis via ER stress, AKT/mTOR, and MAPK pathways in the ovarian cancer cell line.